Prevention And Handling Of Sexual Violence In The Environment Universitas Negeri Makassar - Aulia Raihanah Salwa Ardani; Ririn Nurfaathirany Heri (Cita konsultindo, 2025)
Criminological Analysis of Sexual Violence in Higher Education (Study of the TPKS Law and the Minister of Education, Culture, Research, and Technology Regulation). The purpose of this study is to determine efforts to prevent and handle sexual violence in relation to the TPKS Law and to identify supporting and inhibiting factors in prevention and handling in higher education in relation to the TPKS Law. This study employed a mixed methods approach. Primary data came from field research, including interviews and a questionnaire to determine the number of sexual violence cases in higher education. Secondary data came from library research, including literature and books related to the research. Efforts to prevent and handle sexual violence in the university environment are linked to the TPKS Law and the Minister of Research, Technology and Higher Education Regulation. The supporting factor in the process of preventing and handling sexual violence cases at UNM is the excellent support from the University Leadership. The obstacles in the performance of the PPKS Task Force are the adjustment of time between the PPKS Task Force Team for case examinations due to the busy main tasks so that examinations are often carried out outside campus operating hours, limited facilities and infrastructure also become obstacles in the performance of the UNM PPKS Task Force